Integrated Transmission and Distribution Modelling Using Multi-agent Based Framework - Shukla D.; Singh S.P. (My University, 2025)
Technological changes that enable the widespread adoption of renewable energy-based distributed generation and shift in the source of transportation sectors are introducing nascent challenges and opportunities in power generation, transmission, and distribution systems. Conventionally, the transmission and distribution systems were analyzed in a segregated manner under the assumption that the aggregate load subtended by the distribution systems at the transmission systems would remain constant, but with changing technologies and deployment of large-scale renewable sources of generation along with the increase in electric vehicle charging stations made the load subtended at the transmission level by distribution system to become uncertain with a probability of reverse power-flow. Therefore, an adequate method for analyzing the integrated transmission and distribution systems is to be evolved; in this article, we propose a multi-agent-based system framework for analyzing the integrated transmission and distribution system. The developed framework would be used to analyze the IEEE 9 bus test system at the transmission level and the IEEE 13 Bus test feeder at the distribution level. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.